'Free country, free internet': the symbolic power of technology in the Hungarian internet tax protests. (January 2019) - Ferrari, Elisabetta
In 2014, the Hungarian government announced the introduction of a tax on internet usage. The proposal generated large protests, which led to its eventual withdrawal. In this article, I investigate the puzzling success of the 'internet tax' protests: how could a small tax on internet consumption generate so much contestation? I argue that the internet tax was able to give way to a broader mobilization against the government, because of the symbolic power of the idea of 'the internet', to which different political meanings can be attached. Through interviews with Hungarian activists, I reconstruct how the internet was associated with a mobilizing discourse that I term 'mundane modernity', which reproduces tropes of Western modernity about the equalizing properties of technology, progress, and rationality, while grounding them in the everyday practices of internet use. I then discuss the types of freedom embedded in mundane modernity and assess its political limitations.